Prevalence of sexual dysfunction in women with systemic lupus erythematosus and its related factors - Moghadam, Zahra Behboodi (Reumatologia, 2019)
OBJECTIVES: Systemic lupus erythematosus (SLE) affects all body organs. This disease has marked physiological, mental, and cognitive effects on the patient and results in sexual dysfunction, depression, and decreased self-confidence. This study was conducted to compare sexual function, depression, anxiety, stress, and the related factors in women suffering from SLE. MATERIAL AND METHODS: In this cross-sectional study, 340 women (170 with SLE and 170 healthy) aged 18–49 years were investigated. Convenience sampling was used to select the participants. In this study, a demographic questionnaire, the Depression, Anxiety, and Stress Scales – 21 Items (DASS-21), and the Female Sexual Function Index (FSFI) were applied. Data were analyzed with SPSS 16 using Spearman’s correlation, χ(2), Mann-Whitney, covariance, and multiple regression statistics; p-values less than 0.05 were considered significant. RESULTS: The results showed a significant difference in sexual function between the SLE and healthy groups. According to covariance analysis, the difference remained significant after controlling for confounding factors (stress, depression, anxiety). Moreover, the effect of SLE on the sexual function had a significant correlation with age, life status, number and age of children, economic status, menstruation, duration of marriage, age at diagnosis, disease duration and activity, stress, anxiety, and depression. The results of multiple regression analysis showed that age, disease activity, depression, and life status had the highest correlation with sexual dysfunction in women with SLE. CONCLUSIONS: The results of this study indicated that more attention should be paid to the sexual health of women suffering from SLE as a neglected aspect of their treatment, which requires an interdisciplinary approach to shift the care of these patients from a biomedical model to a biopsychosocial model.